2006
DOI: 10.1371/journal.pone.0000098
|View full text |Cite
|
Sign up to set email alerts
|

A Proof-Of-Principle Study of Epigenetic Therapy Added to Neoadjuvant Doxorubicin Cyclophosphamide for Locally Advanced Breast Cancer

Abstract: BackgroundAberrant DNA methylation and histone deacetylation participate in cancer development and progression; hence, their reversal by inhibitors of DNA methylation and histone deacetylases (HDACs) is at present undergoing clinical testing in cancer therapy. As epigenetic alterations are common to breast cancer, in this proof-of-concept study demethylating hydralazine, plus the HDAC inhibitor magnesium valproate, were added to neoadjuvant doxorubicin and cyclophosphamide in locally advanced breast cancer to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
103
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 64 publications
(76 reference statements)
3
103
0
1
Order By: Relevance
“…CSCs have been identified in several human malignancies, and their relative abundance in clinical cancer specimens has been correlated with disease progression (Arce et al 2006, Schatton et al 2008, Zhou et al 2009. Understanding how CSCs interact with tumor environment, including circulating and locally produced cytokines and hormones, might impact clinical management of different cancer types and development of novel therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…CSCs have been identified in several human malignancies, and their relative abundance in clinical cancer specimens has been correlated with disease progression (Arce et al 2006, Schatton et al 2008, Zhou et al 2009. Understanding how CSCs interact with tumor environment, including circulating and locally produced cytokines and hormones, might impact clinical management of different cancer types and development of novel therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…4 This combination was successfully added to doxorubicin and cyclophosphamide therapy in breast cancer patients as well. 5 The addition of vorinostat to the mammalian target of rapamycin (mTOR) inhibitor temsirolimus improved anti-cancer activity against renal cell carcinoma in vitro and in vivo. 6 Other recent preclinical studies indicated that HDACis such as VPA may sensitize cancer cells, among others PCa cells, to radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Broader examination of a larger array of clinical specimen is warranted to establish further ABCB5 as a universal MMIC marker and robust candidate therapeutic target. Whether related ABC members 26,27 might also represent prospective markers of tumour-initiating cells, or whether ABCB5 might represent such a marker in additional malignancies, such as breast cancer, in which it is known to be clinically expressed and specifically downregulated with epigenetic differentiation therapy 28 , requires further study.…”
mentioning
confidence: 99%